Analysis of Exposure to an Extremely Low Frequency (ELF) 700 μT and 1000 μT Magnetic Fields in Tuna Meat (Euthynnus Affinis C) - Sudarti Sudarti; Karina Laksmiari; Elok Permatasari; Farida Wahyu Ningtyas (Pascasarjana, Mataram University, 2022)
The resistance of tuna meat in a room temperature classed quietly short as it takes approximately 6 hours has encountered a process of decay. Consequently, the technology is needed to increase its durability. This study aims to analyze the exposure to Extremely Low Frequency (ELF) 700 μT and 1000 μT magnetic fields in tuna meat (Euthynnus Affinis C). The sample was 3300 grams of fresh tuna meat, which had been stored in the refrigerator for 4 hours as it was divided into 66 plastic wrappers (50grams), then grouped into three groups. They were the control group (K), the ELF magnetic fields intensity 700 μT (E700) group, and the ELF magnetic fields ELF intensity 1000 μT (E1000) group with variations in an exposure time of 15 minutes, 30 minutes, and 45 minutes. Measurement of pH and assessment of physical condition was carried out on the 5th, 10th, and 15th hours after being exposed to the ELF magnetic fields. The results highlighted the pH value in all groups exposed to the ELF magnetic fields was significantly lower (p < 0.05) than the control group. Meanwhile, the physical condition of tuna exposed to the ELF magnetic fields appeared to be better than the control until the 15th hour of storage. Conclusion: Exposure to an ELF magnetic field with an intensity of 1000 µT for 15 minutes has the potential to increase the physical resistance of tuna until the 15th hour after being exposed to an ELF magnetic field